2020
DOI: 10.1027/1015-5759/a000535
|View full text |Cite
|
Sign up to set email alerts
|

A Psychometric Evaluation of the Short Grit Scale

Abstract: Abstract. Grit, the passion and perseverance for long-term goals, has received attention from personality psychologists because it predicts success and academic achievement. Grit has also been criticized as simply another measure of self-control or conscientiousness. A precise psychometric representation of grit is needed to understand how the construct is unique and how it overlaps with other constructs. Previous research suggests that the Short Grit Scale (Grit-S) has several psychometric limitations, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 34 publications
3
35
0
3
Order By: Relevance
“…Furthermore, consistency demonstrated a high relationship to the common factors of conscientiousness but more specifically related to the self-discipline facet of conscientiousness. Another research also demonstrated that the grit construct overlapped with self-control (Gonzalez et al, 2020). These findings further offer additional evidence on the conceptual resemblance of grit with conscientiousness and self-control.…”
Section: Measurement Issuesmentioning
confidence: 57%
See 1 more Smart Citation
“…Furthermore, consistency demonstrated a high relationship to the common factors of conscientiousness but more specifically related to the self-discipline facet of conscientiousness. Another research also demonstrated that the grit construct overlapped with self-control (Gonzalez et al, 2020). These findings further offer additional evidence on the conceptual resemblance of grit with conscientiousness and self-control.…”
Section: Measurement Issuesmentioning
confidence: 57%
“…The factor structure of original grit model also differs among secondary school and undergraduate student samples (Muenks et al, 2017). Analyses of grit scales (e.g., Short Grit and Original Grit Scales) using item response theory (IRT) approaches also showed mixed evidence regarding the dimensionality of grit with one research demonstrating its unidimensionality (Areepattamannil and Khine, 2018), while other studies demonstrating its multidimensionality (Tyumeneva et al, 2019;Gonzalez et al, 2020). Furthermore, existing measure of grit is plagued by social desirability bias (DiMenichi and Richmond, 2015).…”
Section: Measurement Issuesmentioning
confidence: 99%
“…The Academic Grit Scale we used showed good psychometric properties (Hernández et al, 2016) and demonstrated an essentially unidimensional internal structure (González et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The short version of the Grit Scale (Duckworth et al, 2007) has been questioned in some studies. This well-known and widely-used scale was validated with 2 first-order factors (perseverance of effort and consistency of interests) and 1 second-order factor (grit) (Duckworth & Quinn, 2009), though, recent studies have proposed either a unidimensional structure (Areepattamannil & Khine, 2017;González et al, 2019) or a structure with two distinct factors (Abuhassán & Bates, 2017;Datu et al, 2016;Fosnacht et al, 2019;Wolters & Hussain, 2015). Finally, some authors have found low reliability for the Grit-S scale (Clark & Malecki, 2019).…”
Section: Article In Pressmentioning
confidence: 99%
“…Thus, the grit as a personal factor that the students display interacts with the interpersonal teaching style and must be taken into account. Grit is defined as consistency and perseverance toward long-term goals and describes a sustained commitment to complete a task that involves effort despite failures, setbacks, and adversities (Duckworth et al, 2007), Therefore, it shows a strong relationship with the student's capacity for self-control (González et al, 2019). From recent literature, we know that through grit, students can enhance their own motivation, achievement, and well-being (Cortez et al, 2019;Seong-Lee and Chen-Hsieh, 2019).…”
Section: Social and Personal Triggersmentioning
confidence: 99%